RESULTS AND COMPLICATIONS IN RESECTION OF PITUITARY TUMORS BY NASAL TRANSEPTOSPHENOIDAL ENDOSCOPY - Garavaglia, Federico Ignacio; Paoletti, Oscar; Herrera, Enrique; Pueyrredon , Francisco; Montivero , Agustín; Cabanillas , Juan; Viano, Juan Carlos (Revista Argentina de Neurocirugía, 2021)
OBJECTIVESDescribe results and complications of resection of pituitary tumors by the sphenoid transept endoscopy. Analyze different variables among themselves.METHODSDescriptive, retrospective, longitudinal and observational study, n = 32.Variables related to the approach, closure of the sellar region and complications, histology, resection results and recurrence were studied.RESULTSn = 32 patients, 3 (9.38%) tumors were microadenomas and 29 macroadenomas (90.63%). CSF fistula was observed in 4 patients (12.50%). A rupture of the sellar diaphragm was observed visible during surgery in 6 patients (18.75%). It was observed that of the 16 patients (50%) in the study with visual field alteration, 100% obtained a postsurgical improvement, this being statistically significant (p